“Evaluación de tres concentraciones de Trichoderma spp, nativo como promotor de crecimiento en tres especies hortícolas en el campus Salache – Eloy Alfaro – Latacunga – Cotopaxi 2023.” - Lasluisa Toasa, Heydee Maribel (2023)
The current research was executed at the Salache Campus - Cotopaxi Technical University, Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province, it had as aim by assessing native Trichoderma spp, three concentrations, as a growth promoter in three horticultural species at the research site, it was proposed to assess the vegetative development and determine the three horticultural species best performance with the native Trichoderma spp, three concentrations application. It was used a completely randomized block design (DBCA) in a factorial arrangement AxB (3 x 3), where it is got 9 treatments with four repetitions, resulting in a 36 experimental units total. The assessed variables were: capture percentage, height, leaves number, weight, polar diameter, equatorial diameter and yield. For the data analysis, it was performed a statistical analysis (ANOVA), in the variation sources, which indicated statistical significance, it was performed a 5% Tukey test, while for the variables, which did not present statistical significance, it was performed tables of averages. For the height, the concentration (10^8) was the one with 51.63 cm for celery; 22.38 cm in broccoli and 15.25 cm in cauliflower; in number of sheets with 14.25; 8.25 and 8.75 for celery, broccoli and cauliflower. The highest yield was got in the T8 concentration treatment (10^8) in cauliflower with an average 4392.5 kg/ha, it followed by the T7 concentration (10^8) in broccoli with an average 4330 kg/ha and finally the T9 concentration (10^8) in celery with an average value 2480 kg/ha.